Electrochemical Deposition of Fe-Co-Ni Samples with Different Co Contents and Characterization of Their Microstructural and Magnetic Properties - Long, Van Cao; Saraç, Umut; Baykul, Mevlana Celalettin; Luong Duong Trong; Talu, Stefan; Dung Nguyen Trong; Saraç, Umut (Mdpi, 2022)
In this study, to explore the effect of Co contents on the electroplated Fe-Co-Ni samples, three different Fe-Co-33-Ni-62, Fe-Co-43-Ni-53, and Fe-Co-61-Ni-36 samples were electrochemically grown from Plating Solutions (PSs) containing different amounts of Co ions on indium tin oxide substrates. Compositional analysis showed that an increase in the Co ion concentration in the PS gives rise to an increment in the weight fraction of Co in the sample. In all samples, the co-deposition characteristic was described as anomalous. The samples exhibited a predominant reflection from the (111) plane of the face-centered cubic structure. However, the Fe-Co-61-Ni-36 sample also had a weak reflection from the (100) plane of the hexagonal close-packed structure of Co. An enhancement in the Co contents caused a strong decrement in the crystallinity, resulting in a decrease in the size of the crystallites. The Fe-Co-33-Ni-62 sample exhibited a more compact surface structure comprising only cauliflower-like agglomerates, while the Fe-Co-43-Ni-53 and Fe-Co61-Ni36 samples had a surface structure consisting of both pyramidal particles and cauliflower-like agglomerates. The results also revealed that different Co contents play an important role in the surface roughness parameters. From the magnetic analysis of the samples, it was understood that the Fe-Co-61-Ni-36 sample has a higher coercive field and magnetic squareness ratio than the Fe-Co-43-Ni-53 and Fe-Co-33-Ni-62 samples. The differences observed in the magnetic characteristics of the samples were attributed to the changes revealed in their phase structure and surface roughness parameters. The obtained results are the basis for the fabrication of future magnetic devices.
Keywords: Cauliflower-Like Agglomerates; Co Contents; Crystallinity; Fe-Co-Ni Thin Film Samples; Magnetic Properties; Phase Structure; Pyramidal Particles; Roughness Parameters